The Natural Cytotoxicity Receptor NKp44 (NCR2, CD336) Is Expressed on the Majority of Porcine NK Cells Ex Vivo Without Stimulation - Mair, Kerstin H.; Crossman, Assiatu J.; Wagner, Bettina; Babasyan, Susanna; Noronha, Leela; Boyd, Patricia; Zarlenga, Dante; Stadler, Maria; van Dongen, Katinka A.; Gerner, Wilhelm; Saalmüller, Armin; Lunney, Joan K. (Frontiers in Immunology, 2022)
Natural killer (NK) cells have been studied extensively in humans and mice for their vital role in the vertebrate innate immune system. They are known to rapidly eliminate tumors or virus infected cells in an immune response utilizing their lytic properties. The natural cytotoxicity receptors (NCRs) NKp30 (NCR3), NKp44 (NCR2), and NKp46 (NCR1) are important mediators of NK-cell cytotoxicity. NKp44 expression was reported for NK cells in humans as well as in some non-human primates and found exclusively on activated NK cells. Previously, no information was available on the NKp44 protein expression and its role in porcine lymphocytes due to the lack of species-specific monoclonal antibodies (mAbs). For this study, porcine-specific anti-NKp44 mAbs were generated and their reactivity was tested on blood and tissue derived NK cells in pigs of different age classes. Interestingly, NKp44 expression was detected ex vivo already on resting NK cells; moreover, the frequency of NKp44+ NK cells was higher than that of NKp46+ NK cells in most animals analyzed. Upon in vitro stimulation with IL-2 or IL-15, the frequency of NKp44+ NK cells, as well as the intensity of NKp44 expression at the single cell level, were increased. Since little is known about swine NK cells, the generation of a mAb (clone 54-1) against NKp44 will greatly aid in elucidating the mechanisms underlying the differentiation, functionality, and activation of porcine NK cells.